2003
DOI: 10.1017/s1047951103000581
|View full text |Cite
|
Sign up to set email alerts
|

Hoarseness after pulmonary arterial stenting and occlusion of the arterial duct

Abstract: We report a 12-year-old girl who had multiple congenital cardiac lesions, specifically an arterial duct, left pulmonary arterial stenosis, an atrial septal defect in the oval fossa, and mild Ebstein's malformation of the tricuspid valve. Therapeutic transcatheter intervention was performed to stent the left pulmonary artery, occlude the arterial duct with a coil, and place a device to close the atrial septal defect. Subsequent to the catheterization, she complained of hoarseness, which was shown to be due to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
1
8
2
Order By: Relevance
“…This condition suggests us that LRLN paralysis may have been caused by the device. This is similar to the case reported by Assaqqat et al (6) wherein LRLN was compressed between the LPA stent and the PDA coil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This condition suggests us that LRLN paralysis may have been caused by the device. This is similar to the case reported by Assaqqat et al (6) wherein LRLN was compressed between the LPA stent and the PDA coil.…”
Section: Discussionsupporting
confidence: 91%
“…Cardiovascular conditions leading to Ortner’s syndrome are aortic diseases; left atrial disorders; and congenital heart diseases, including atrial septal defect, ventricular septal defect, total anomalous pulmonary venous connection, PDA, double outlet right ventricle, left main coronary artery arising from the pulmonary artery, and idiopathic pulmonary hypertension (2). It has also been reported that cardiovascular interventions cause iatrogenic Ortner’s syndrome were coil closure of PDA, endoluminal treatment of a thoracic aortic aneurysm, transcatheter ablation of atrial fibrillation, and stenting of the left pulmonary artery (1-6).…”
Section: Discussionmentioning
confidence: 99%
“…Similar complications have also been described during percutaneous interventional procedures, such as transvenous insertion of a permanent endocardial pacemaker [5], transcatheter ablation of atrial fibrillation [6], stenting of the left pulmonary artery [7] and coil closure of patent ductus arteriosus (PDA) [7][8][9] with analogous pathogenetic mechanisms. Particularly, in the PDA closure cases, an oversized or inappropriate coil implantation, by distorting the slender PDA, caused the angulation of the pliable PDA itself and precipitated the impingement on the left RLN.…”
Section: Discussionmentioning
confidence: 62%
“…Because there have been only two cases of LRLNP after LPA stent insertion, 1 2 the risk factors are unknown. Tetralogy of Fallot (TOF) frequently accompanies LPA stenosis and vice versa.…”
mentioning
confidence: 99%
“…Assaqqat et al 1 reported LRLNP after a concurrent intervention on the LPA, PDA and ASD. They assumed that the LRLN might have been entrapped between the two devices in the PDA and LPA.…”
mentioning
confidence: 99%